2019
DOI: 10.1101/827881
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromatin organization in early land plants reveals an ancestral association between H3K27me3, transposons, and constitutive heterochromatin

Abstract: Genome packaging by nucleosomes is a hallmark of eukaryotes. Histones and the pathways that deposit, remove, and read histone modifications are deeply conserved. Yet, we lack information regarding chromatin landscapes in extant representatives of ancestors of the main groups of eukaryotes and our knowledge of the evolution of chromatin related processes is limited. We used the bryophyte Marchantia polymorpha, which diverged from 3 vascular plants 400 Mya, to obtain a whole chromosome genome assembly and explor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(98 citation statements)
references
References 96 publications
6
88
0
Order By: Relevance
“…however, in reproductive tissues and mutants where DNA methylation is reduced, this mark also accumulates at TEs (Deleris et al, 2012;Weinhofer et al, 2010). Other studies have also reported the accumulation of H3K27me3 at transposon sites in plant species with reduced levels of DNA methylation (Montgomery et al, 2020), as well as in mammal somatic and reproductive tissues which also show reduced levels of DNA methylation (Hanna et al, 2019;Reddington et al, 2014;Saksouk et al, 2014). However, our data do not fully support the idea that the deposition of this chromatin mark acts as a compensatory system to silence hypomethylated TEs (Deleris et al, 2012;Hanna et al, 2019).…”
Section: Discussionmentioning
confidence: 86%
“…however, in reproductive tissues and mutants where DNA methylation is reduced, this mark also accumulates at TEs (Deleris et al, 2012;Weinhofer et al, 2010). Other studies have also reported the accumulation of H3K27me3 at transposon sites in plant species with reduced levels of DNA methylation (Montgomery et al, 2020), as well as in mammal somatic and reproductive tissues which also show reduced levels of DNA methylation (Hanna et al, 2019;Reddington et al, 2014;Saksouk et al, 2014). However, our data do not fully support the idea that the deposition of this chromatin mark acts as a compensatory system to silence hypomethylated TEs (Deleris et al, 2012;Hanna et al, 2019).…”
Section: Discussionmentioning
confidence: 86%
“…So far, most studies in chromatin profiling in plants have been limited to relatively small genomes (e.g. different angiosperms, a moss, and a liverwort) ( Zhang et al , 2007 ; Widiez et al , 2014 ; Hussey et al , 2017 ; Latrasse et al , 2017 ; Chica et al , 2017 ; Lü et al , 2018 ; Montgomery et al , 2020 ). However, genome-wide analysis in gymnosperms has remained a challenge due to the large genome sizes of these species ( Pellicer et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most genome-wide analyses of histone modifications in plants have been accomplished in species with relatively small genomes, with the exception of maize, barley, and wheat ( Zhang et al , 2007 ; Makarevitch et al , 2013 ; Widiez et al , 2014 ; Baker et al , 2015 ; Hussey et al , 2017 ; Latrasse et al , 2017 ; Chica et al , 2017 ; Lü et al , 2018 ; Qi et al , 2018 ; Li et al , 2019 ; Montgomery et al , 2020 ). In contrast to many angiosperm studies, genome-wide chromatin profiling in other plant species has been limited to moss, liverwort, and unicellular algae ( Widiez et al , 2014 ; Mikulski et al , 2017 ; Montgomery et al , 2020 ). Gymnosperm species have generally very large (4–30 Gbp) and poorly assembled genomes, making this type of profiling laborious and challenging.…”
Section: Introductionmentioning
confidence: 99%
“…For GO term and protein family enrichment analysis, the algorithm and annotations were as described previously [91]. Gene names from Marchantia v5.1 [92] was assigned in accordance to gene corresponding table available at http://marchantia.info/nomenclature/ [2]. Genes were annotated using information nomenclature previously published [93] or available at MarpolBase.…”
Section: Methodsmentioning
confidence: 99%